Lead Structures for Applications in Photodynamic Therapy. 6. Temoporfin Anti-Inflammatory Conjugates to Target the Tumor Microenvironment for In Vitro PDT - Rogers, Luke; Sergeeva, Natalia N.; Paszko, Edyta; Vaz, Gisela M. F.; Senge, Mathias O. (PLOS ONE, 2015)
Due to the ongoing development of clinical photodynamic therapy (PDT), the search continues for optimized photosensitizers that can overcome some of the side effects associated with this type of treatment modality. The main protagonists being: post-treatment photosensitivity, due to only limited cellular selectivity and post-treatment tumor regrowth, due to the up-regulation of pro-inflammatory agents within the tumor microenvironment. A photosensitizer that could overcome one or both of these drawbacks would be highly attractive to those engaged in clinical PDT. Certain non-steroidal anti-inflammatory drugs (NSAIDs) when used in combination with PDT have shown to increase the cytotoxicity of the treatment modality by targeting the tumor microenvironment. Temoporfin (m-THPC), the gold standard chlorin-based photosensitizer (PS) since its discovery in the 1980’s, has successfully been conjugated to non-steroidal anti-inflammatory compounds, in an attempt to address the issue of post-treatment tumor regrowth. Using a modified Steglich esterification reaction, a library of “iPorphyrins” was successfully synthesized and evaluated for their PDT efficacy.